PENGARUH REKRUTMEN TERHADAP KINERJA KARYAWAN DI KOPERASI LEMBAGA PENGEMBANGAN PERBANKAN INDONESIA - Putri Sarirati; Fandy Baskara (Sekolah Tinggi Manajemen IMMI Jakarta, 2019)
This study aims to determine the effect of recruitment on improving cooperative performance. This analysis uses the independent variable, recruitment, and the dependent variable is employee performance.The population in this study were all supervisors, managers and associations of Indonesian banking development cooperatives. Samples were conducted using the non-probability sampling method using saturated samples obtained 30 people as samples. The type of data used is primary data. The testing method in this thesis uses IBM SPSS 22 processing. The results of the questionnaire have been tested for validity, reliability testing, data normality test, regression analysis and hypothesis testing.The results of the study prove that the proposed partial hypothesis is accepted because it shows significant test results. This means a significant increase in employee performance by 81.0% while 19.0% requires other factors.